(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Yalangtosh Bahadur was born in 1576 (according to other sources in 1578) to the son of Boykhodjibiy, ruler of Nurota, founder of the Olchin tribe. According to his contemporary Mahmud ibn Wali’s "Bahr al-Asrar fi manukib al-akhyor": "The Emir’s original horse was Khatai Bahadur, and "Yalangtosh" was his nickname". In history, this breed is mentioned by such names as Yalangtosh ibn Boykhodjibiy, Yusuf Yalangtosh, Abdukarimbiy, Nizamiddin. "Yalangtosh" (meaning "bare-breasted man") was awarded the honor of Bahadur for fighting in a saddle where his chest was not covered with a shield in battles. This article describes the history of Yalangtosh Bahadur’s diplomatic life, political activity and military ability.